2014
DOI: 10.1186/1752-1505-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, forced displacement and health in Sri Lanka: a review of the research landscape

Abstract: Sri Lanka has recently emerged from nearly three decades of protracted conflict, which came to an end five years ago in 2009. A number of researchers have explored the devastating effect the conflict has had on public health, and its impact on Sri Lanka’s health system - hailed as a success story in the South Asian region. Remarkably, no attempt has been made to synthesize the findings of such studies in order to build an evidence-informed research platform. This review aims to map the ‘research landscape’ on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 63 publications
2
45
0
Order By: Relevance
“…Mental disorders most commonly attributed to conflict in the region are depression, anxiety, and post-traumatic stress disorder, with variations across countries (table 1 ). 9 41 42 These variations may be influenced by factors such as the nature of the conflict (ethnic, religious, ideological), its duration (acute, protracted, recurrent), the region (urban, rural), and forced displacement. However, higher prevalence of mental disorder shows a host of similar sociodemographic associations across countries such as older age, female sex, displacement, being widowed/divorced, low income/education, and food insecurity.…”
Section: Key Messagesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mental disorders most commonly attributed to conflict in the region are depression, anxiety, and post-traumatic stress disorder, with variations across countries (table 1 ). 9 41 42 These variations may be influenced by factors such as the nature of the conflict (ethnic, religious, ideological), its duration (acute, protracted, recurrent), the region (urban, rural), and forced displacement. However, higher prevalence of mental disorder shows a host of similar sociodemographic associations across countries such as older age, female sex, displacement, being widowed/divorced, low income/education, and food insecurity.…”
Section: Key Messagesmentioning
confidence: 99%
“…Evidence from Sri Lanka shows an increased risk of infectious diseases such as tuberculosis, polio, malaria, and diarrhoeal diseases; increased war related physical injuries and disability; child health problems such as malnutrition, developmental disorders, and infections; reproductive health disorders and gender based/interpersonal violence; and increased numbers of children and adults with war related mental health problems. 9 Some South Asian countries such as Pakistan and Afghanistan continue to experience chronic conflict, and others such as Nepal and Sri Lanka are yet to recover fully from the lingering effects of protracted conflict on the health of their populations.…”
Section: Health Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term impact of the war, for instance, on the psycho-social well-being of the public (Somasundaram, 2010;Siriwardhana et al, 2015;Keraite et al, 2016), including people with forced displacement status (Husain et al, 2011;Siriwardhana and Wickramage, 2014), are reported. In addition, some international organisations, such as the WHO (Siriwardhana et al, 2013), and researchers (Taira et al, 2010) suggest programmes that strengthen the health system in the Northern Province of Sri Lanka, while research underlines the importance of community resilience (Somasundaram and Sivayokan, 2013).…”
Section: Introductionmentioning
confidence: 99%